The Importance of Education and Development Prospects in the Field of Tourism - Alieva, M. T.; Tokhirjon, Abduganiyev (European Journal of Life Safety and Stability (2660-9630), 2023)
I hope this article will make a great contribution to the development of tourism by integrating the education and tourism system, changing students’ views on tourism in their lives, and interpreting new ideas. For example, we see that school graduates do not know tourist books or places. In interpreting my ideas, I would like tourism to be taught as a subject in the final grades of secondary schools. Another way to develop tourism in the current conditions of globalization is to attract tourists by advertising holidays or ancient places on social networks.